Constructive deviance as a driver for performance in retail. (May 2016) - Mertens, Willem; Recker, Jan; Kummer, Tyge-F.; Kohlborn, Thomas; Viaene, Stijn
Abstract: A growing body of research is concerned with deviance in the workplace. While much research has explored negative forms of deviance, we examine constructive deviance: behaviour that deviates from salient norms and benefits the reference group. We empirically explore manifestations, determinants and performance outcomes of constructive deviance in standardised work processes. We do this through a mixed-methods study in bakery trading departments of an Australian retailer. We illustrate that constructive deviance occurs in these settings and show that some manifestations of constructive deviance improve organisational performance and pave the way for applying constructive deviance as a strategic tool in retail.